Reflection increases belief in God through self-questioning among non-believers - Onurcan Yilmaz; Ozan Isler (Judgment and Decision Making, 2019)
The dual-process model of the mind predicts that religious belief will be stronger for intuitive decisions, whereas reflective thinking will lead to religious disbelief (i.e., the Intuitive Religious Belief Hypothesis). While early research found intuition to promote and reflection to weaken belief in God, more recent attempts found no evidence for the intuitive religious belief hypothesis. Many of the previous studies are underpowered to detect small effects, and it is not clear whether the cognitive process manipulations used in these failed attempts worked as intended. We investigated the influence of intuitive and reflective thought on belief in God in two large-scale preregistered experiments (N = 1,602), using well-established cognitive manipulations (i.e., time-pressure with incentives for compliance) and alternative elicitation methods (between and within-subject designs). Against our initial hypothesis based on the literature, the experiments provide first suggestive then confirmatory evidence for the Reflective Religious Belief Hypothesis. Exploratory examination of the data suggests that reflection increases doubts about beliefs held regarding God’s existence. Reflective doubt exists primarily among non-believers, resulting in an overall increase in belief in God when deciding reflectively.